Cognitive Psychology - Robert L. Solso; Otto H. MacLin; M. Kimberly MacLin (New Delhi Affiliated East- West Press Private Limited)
One of the top sellers in the field, Cognitive Psychology is well-written, humorous, and remains one of the most comprehensive and balanced books in the area of cognition. MacLin and MacLin, inheriting the book from the late Robert L. Solso, boldly revised and reorganized the Eighth Edition to reflect emerging trends in the field, while retaining the strengths that made it one of the most popular books in the field.
Keywords: Psychology